The Impact of Kahoot on English Vocabulary Acquisition: A Study of Moroccan High School Students - Boudinar, Abdessamad; Lagmidi, Abdelmounim (International Journal of Language and Literary Studies, 2025)
In an era where digital engagement shapes modern education, integrating gamification into language learning has emerged as a powerful tool to enhance student engagement and learning outcomes. This study investigates the impact of Kahoot, a platform for learning through games, on the English language vocabulary acquisition of Moroccan high school students. A quasi-experimental design with 80 students (40 per group) was used. Students sat for vocabulary pre- and post-tests (15 points per test), and the data were processed using descriptive and inferential statistics. The findings revealed that Kahoot significantly improved vocabulary acquisition among students in the experimental group compared to traditional teaching methods. This study highlights the instructional value of gamification tools like Kahoot in vocabulary instruction and provides pedagogical implications and suggestions for integrating digitally gamified tools in the language classroom.